Housing affordability: Ireland in a cross-country context - Wendy Disch; Rachel Slaymaker (The Economic and Social Research Institute (ESRI), 2023)
Persistent, structural housing affordability challenges in Ireland have been well documented for particular groups (private renters, low to middle income households and those in urban areas (Corrigan et al., 2019)). Recent research has also documented the access to credit constraints faced by first-time buyers and the challenges associated with accumulating a deposit and tight loan-to-income limits (McQuinn et al., 2021; Kelly and Mazza, 2019; Slaymaker et al., 2022). However, these challenges are not unique to Ireland, and worsening affordability pressures and falling homeownership rates have been highlighted globally (Demographia, 2022) as the share of household income spent on housing costs has risen over-time (OECD, 2021a). This paper aims to better contextualise the housing affordability challenges faced in Ireland by examining how key affordability indicators such as housing-payment-cost-to-income ratios for Irish households (across tenures, incomes, household composition, urbanisation and age) compare with those in 14 other European countries. This analysis is based on 2019 Eurostat cross-country Survey on Living Conditions (EU-SILC) data to avoid any potential distortions in affordability indicators as a result of differing COVID-19 income support policy responses across countries. A considerable benefit of using nationally representative household level microdata is that they provide a more complete affordability picture for the full stock of tenants and mortgage holders compared to frequently cited rent/ house price index measures based solely on new tenancies/recent movers.
Keywords: 330; Wohnungsmarkt; Immobilienpreis; Irland